PENGARUH KECERDASAN EMOSIONAL DAN LITERASI DIGITAL TERHADAP KINERJA PEGAWAI GENERASI Z KOTA BIMA - Jaenab Jaenab; Novi Kadewi Sumbawati; Amirul Mukminin (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2025)
The purpose of this study was to determine the positive and significant influence of emotional intelligence and digital literacy on the performance of Generation Z employees in Bima City. This research is a quantitative study. This type of research is associative with the population used in this study, namely all Generation Z employees in Bima City. The sample used in this study was Generation Z employees in Bima City totaling 100 employees. The sampling technique in this study used purposive sampling based on criteria, the research instrument used was a questionnaire with a Likert scale. The analysis tool used in this study used multiple linear regression analysis using SPSS version 21. The results of this study are: 1) Emotional Intelligence does not have a positive and significant effect on the Performance of Generation Z Employees in Bima City. 2) Digital Literacy has a positive and significant effect on the Performance of Generation Z Employees in Bima City. 3) Emotional Intelligence and Digital Literacy have a positive and significant effect on the Performance of Generation Z Employees in Bima City.